Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Trans Retail Indonesia - Johan Hursepuny; Sita Dewi; Tania Rizki; Dwi Listyowati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
The purpose of this study was to determine how much influence the leadership style and work discipline have an effect on the employee performance of Carrefour Mangga Dua.The results of this study explain that partially the leadership style with –t table < t count < t table or -2,04 < 0.155 < 2.04, means that there is no influence of leadership style on employee performance. Work discipline with t count > t table or 3.421 > 2.04, means that there is an effect of work discipline on employee performance. The results of this study explain that simultaneously the value of F count > the F table or 8.946 > 3.32. It means that the two independent variables (leadership style and work discipline) together have a significant effect on employee performance variables.